Sentido da vida e da morte e o grau de religiosidade em pessoas recuperadas da Covid-19 - Ferreira, Vitória da Cunha (2021)
Nowadays, the pandemic of the new SARS-CoV-2 coronavirus provoked reflections on the importance of religiosity and questioned the human being about the meaning of existence and death. From this, the present study aimed to understand how those recovered from COVID-19 in the metropolitan region of Patos perceive Death, Religiosity and the Meaning of Life, considering their experiences during the period of illness and recovery. Therefore, a field research was carried out with a quanti-qualitative approach, with the collaboration of 20 participants, 10 men (50%) and 10 women (50%), aged between 18 and 62 years (M=32 .4; SD=12.67), most of which had COVID-19 in its mild form (45%) and were treated at home (80%). In this scenario, the following instruments were used: Religious Attitudes Scale (EAR-20), semi-structured interview and biosociodemographic questionnaire. Regarding data analysis, descriptive and inferential statistics were used, such as the Student t test for the quantitative part, and the Word Cloud in the IRAMUTEQ software and Content Analysis according to Bardin (2011) for qualitative data. The results show that women had statistically higher scores in the domains of religious corporeality [t (18) = 5.708; p < 0.001)] and religious feeling [t (11) = 3.827; p < 0.05)] when compared to men. On the other hand, in the qualitative stage, it was found that individuals understood death from a positive and negative perspective and understood religiosity as a means of coping with the disease process. Furthermore, with regard to the meaning of life, creative, experiential and attitudinal values were found in the interviewees' reports. Thus, the identified results were discussed through the scientific literature, especially in the light of logotherapy and existential analysis authored by Viktor Frankl.